Examining the Relationships between Student Veterans and Faculty Members - Sierra C Sullivan; Peggy Ann Everett (Adult Education Research Conference, 2018)
The researchers conducted a pilot study to guide a doctoral student in her dissertation topic. They conducted interviews with faculty members and student servicemembers/veterans to explore their experiences inside and outside the classroom.
Keywords: Student Veterans; Faculty; Relationships; Student Servicemembers/Veterans (SSM/V)